Enhanced biogas production from Lantana camara via bioaugmentation of cellulolytic bacteria. (November 2021) - Sinha, Debasree; Banerjee, Sandipan; Mandal, Subhrangshu; Basu, Aman; Banerjee, Aishiki; Balachandran, Srinivasan; Chandra Mandal, Narayan; Chaudhury, Shibani
Graphical abstract: Highlights: Utilization of invasive weed Lantana camara for biogas production. Bioaugmentation of cellulolytic soil and termite gut bacteria for enhanced biogas production. Microbacterium sp. DSB1 emerged as a novel biogas generating termite gut bacteria. 56% higher biogas producing proficiency by Arthrobacter sp. DSB12 (980 l/kg VS) compared to control sets. Sustainable and renewable green-energy generation as biogas to fulfil the electricity and cooking gas demands. Abstract: A study was designed to isolate cellulolytic bacteria from termite-gut and soil, optimizing their cellulase production to enhance biogas generation, using Lantana camara as a substrate. Out of 57 bacteria screened, two isolates DSB1 and DSB12, showed significant cellulolytic activity. 16S rRNA based methods identified these isolates as Microbacterium sp. and Arthrobacter sp. respectively. Maximum cellulase activity of 1.26 ± 0.044 U/ml and 1.31 ± 0.052 U/ml for DSB1 and DSB12 was observed at pH 7 and 7.2 under 35⁰C and 37⁰C, respectively. The L. camara biomass substrate with cow dung as an inoculum, bioaugmented with DSB1 and DSB12 separately, was tested for biogas production, producing 950 l/kg and 980 l/kg VS biogas with 57% and 60% methane, respectively. DSB1 and DSB12 revealed as potent cellulase producers that can be harnessed in the anaerobic digester for biomass conversion practices for enhanced biogas production.